2019
DOI: 10.1096/fj.201900627r
|View full text |Cite
|
Sign up to set email alerts
|

Heparinoid sevuparin inhibitsStreptococcus‐induced vascular leak through neutralizing neutrophil‐derived proteins

Abstract: Acute lung injury (ALI) and respiratory distress can develop as a consequence of sepsis with pathogens such as group A Streptococcus (GAS). In the pathogenesis of sepsis‐associated ALI, endothelial barrier disruption brought on by phagocyte activation is considered a causative factor. Here, we find that sevuparin, a heparinoid with low anticoagulant activity, prevents neutrophil‐induced lung plasma leakage in a murine model of systemic inflammation evoked by heat‐killed GAS (hkGAS). Furthermore, using human ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…One such heparinoid compound has been successfully tested clinically in phase I/II studies of Plasmodium falciparum malaria disease (Leitgeb et al 2017). This molecule also prevented neutrophil-induced lung plasma leakage in a murine sepsis model (Rasmuson et al 2019). As already mentioned, neutrophil-mediated pathology is of central importance in acute lung injury.…”
Section: Heparin and Heparinoid Compoundsmentioning
confidence: 57%
“…One such heparinoid compound has been successfully tested clinically in phase I/II studies of Plasmodium falciparum malaria disease (Leitgeb et al 2017). This molecule also prevented neutrophil-induced lung plasma leakage in a murine sepsis model (Rasmuson et al 2019). As already mentioned, neutrophil-mediated pathology is of central importance in acute lung injury.…”
Section: Heparin and Heparinoid Compoundsmentioning
confidence: 57%
“…Rasmuson et al revealed that sevuparin, a heparinoid with low anticoagulant activity, prevented neutrophil-induced lung plasma leakage in a murine model of systemic inflammation evoked by heat-killed group A Streptococcus ( 109 ). Their results demonstrated that sevuparin could interact with neutrophil secretion including serprocidins, S100 proteins and histone H4 and thus attenuate the disruptive effect of histone on endothelial integrity, suggesting a potential therapeutic of sevuparin in acute neutrophilic inflammation like sepsis.…”
Section: Circulating Histones In Sepsis As Potential Therapeutic Targmentioning
confidence: 99%
“…These observations stimulated the development of heparinoids that lack anticoagulant properties while keeping their anti-inflammatory effects (Rao et al 2010). Indeed, sevuparin, a low-anticoagulant heparin analog, inhibited NE and histone H4, proteins associated with NETs (Rasmuson et al 2019). In another study, non-anticoagulant heparin prevented histone-mediated cytotoxicity and improved survival in a murine sepsis model (Wildhagen et al 2014).…”
Section: Heparinmentioning
confidence: 99%